Heterosis and Inbreeding Depression for Seed Yield and its Contributing Characters in Indian Mustard [Brassica juncea (L.) Czern & Coss.] - Patel, J. R.; Patel, D. K.; Patel, A. M.; Patel, P. J.; Prajapati, K. N. (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted in compact family block design with three replications during rabi (October, 2022–March, 2023) 2022–23 at Centre for Oilseeds Research, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, Gujarat, India to study heterosis and inbreeding depression for seed yield and its contributing characters in Indian mustard [Brassica juncea (L.) Czern & Coss.]. The expression of heterosis and heterobeltiosis was maximum for seed yield plant-1 followed by number of siliquae plant-1, number of secondary branches plant-1 and 1000 seed weight. For seed yield plant-1, cross III (GDM 4×PM 30), cross IV (GM 6×PDZM 31) and cross VI (RB 50×NUDHYJ 4) depicted significant and positive relative heterosis and heterobeltiosis. The cross III also showed significant and desirable estimates of relative heterosis and/or heterobeltiosis for days to flowering, days to maturity, number of primary and secondary branches plant-1, number of siliquae on main branch, number of siliquae plant-1 and 1000 seed weight, while cross IV exhibited significant and desirable relative heterosis and/or heterobeltiosis for days to flowering, days to maturity, number of secondary branches plant-1, number of siliquae plant-1, length of siliqua and oil content. The magnitude of inbreeding depression was found positive and significant for days to maturity, plant height and erucic acid in cross VI. While significant negative inbreeding depression was observed for 1000 seed weight (cross V); oil content (cross VI); oleic acid (cross II and V) and linoleic acid (cross VI), hence these crosses would likely to yield transgressive segregants for the characters under consideration.